River channel planforms and floodplains: a study in the Wessex landscape. (2nd January 2018) - Cook, Hadrian
ABSTRACT: For south 'Wessex', despite complexity evident on the ground, there is little research that directly links river channel form with historic economic development; that is, channel genesis and planforms are seldom discussed in relation to landscape development within valleys. Of specific interest are relationships linking channel topography, artificial cuts and floodplains with development associated with mills, water-meadows, artificial watercourses and gravel extraction. These are an outcome of a strong regional culture of economic development including water management. It is demonstrated that river planforms within the valleys determine the location of fixed assets and there is a strong relationship between soils and floodplain development. It is concluded that there is an intricate continuum between perceived 'natural' fluvial process and human-influenced environmental change, and that genetic interpretation of river channel forms presents a challenge for landscape historians.